Routing Protocols in Scale-Free Networks: A Survey - Pearl Antil; Amita Malik (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Scale-Free Network is a connected network of inhomogeneous nodes with a power-law degree distribution. The ubiquitous presence of scale-free networks has initiated the interest of many profound researchers to study the behaviour and dynamics of these networks. This article discusses different routing challenges encountered in the design of scale-free routing protocols. The scale-free routing algorithms have been grouped into three categories based on topology information used in the network, network dynamics and routing strategy for better comprehension. The paper analyses these routing algorithms highlighting their relative merits and demerits. It also suggests various application domains pertaining to the existing routing algorithms. The article also highlights some open research issues to point to future research directions which can help to design efficient scale-free routing algorithms